Neutralizing Antibodies Against Interferon-Beta in Korean Patients with Multiple Sclerosis - Hyun, Jae-Won (J Clin Neurol, 2018)
BACKGROUND AND PURPOSE: Patients treated with interferon-beta (IFN-β) can develop neutralizing antibodies (NAbs) against IFN-β that can negatively affect the therapeutic response. This study assessed the prevalence of NAbs and the impact of NAb positivity on the therapeutic response to IFN-β in Korean patients with multiple sclerosis (MS). METHODS: This was a multicenter study involving 150 MS patients from 9 Korean medical centers who were treated with IFN-β for at least 6 months. Sera that had not been influenced by acute treatment were assessed for NAbs using a luciferase reporter gene assay. To evaluate the association between persistent positivity for NAbs and disease activity, NAbs were tested at 2 different time points in 75 of the 150 patients. Disease activity was defined as the presence of clinical exacerbations and/or active MRI lesions during a 1-year follow-up after NAb positivity was confirmed. RESULTS: NAbs were found in 39 of the 150 (26%) MS patients: 30 of the 85 (35%) who were treated with subcutaneous IFN-β-1b, 9 of the 60 (15%) who were treated with subcutaneous IFN-β-1a, and 0 of the 5 (0%) who were treated with intramuscular IFN-β-1a. Thirty of the 39 patients exhibiting NAb positivity were tested at different time points, and 20 of them exhibited persistent NAb positivity. Disease activity was observed more frequently in patients with persistent NAb positivity than in those with transient positivity or persistent negativity [16/20 (80%) vs. 4/55 (7%), respectively; p<0.001]. When disease activity was compared between patients with persistent and transient NAb positivity, the difference was unchanged and remained statistically significant [16/20 (80%) vs. 2/10 (20%), p=0.004]. CONCLUSIONS: These results further support that persistent NAb positivity is associated with disease activity in MS patients treated with IFN-β.